Palaeopermeability structure within fault-damage zones: A snap-shot from microfracture analyses in a strike-slip system. (February 2016) - Gomila, Rodrigo; Arancibia, Gloria; Mitchell, Thomas M.; Cembrano, Jose M.; Faulkner, Daniel R.
Abstract: Understanding fault zone permeability and its spatial distribution allows the assessment of fluid-migration leading to precipitation of hydrothermal minerals. This work is aimed at unraveling the conditions and distribution of fluid transport properties in fault zones based on hydrothermally filled microfractures, which reflect the ''frozen-in'' instantaneous advective hydrothermal activity and record palaeopermeability conditions of the fault-fracture system. We studied the Jorgillo Fault, an exposed 20 km long, left-lateral strike-slip fault, which juxtaposes Jurassic gabbro against metadiorite belonging to the Atacama Fault System in northern Chile. Tracings of microfracture networks of 19 oriented thin sections from a 400 m long transect across the main fault trace was carried out to estimate the hydraulic properties of the low-strain fault damagezone, adjacent to the high-strain fault core, by assuming penny-shaped microfractures of constant radius and aperture within an anisotropic fracture system. Palaeopermeability values of 9.1*10 −11 to 3.2*10 −13 m 2 in the gabbro and of 5.0*10 −10 to 1.2*10 −13 m 2 in the metadiorite were determined, both decreasing perpendicularly away from the fault core. Fracture porosity values range from 40.00% to 0.28%. The Jorgillo Fault has acted as a left-lateral dilational fault-bend, generating large-scale dilation sites north of the JF during co-seismic activity. Highlights: We examine the architecture and hydraulic properties of a brittle fault exposed in Northern Chile. Structural parameters of the fault-related microfracture network were documented. High palaeopermeability and porosity values for the Jorgillo Fault were estimated. Two deformation processes are identified following structural-hydraulic properties. The fault acted as a dilational fault-bend, creating co-seismic dilation sites.